Evaluation of Logistics Service Quality Using the Zone of Tolerance (ZOT) Method: An Empirical Study of a Local Logistics Transportation Company in Makassar, Indonesia - Adi Bangun; Sulton Junaidi (Journal of Managerial Sciences and Studies, 2026)
As a maritime country, Indonesia requires an integrated logistics transportation system to support both domestic and international trade activities. This study aims to evaluate logistics service quality in a local logistics transportation company in Makassar using the Zone of Tolerance (ZOT) approach. The study investigates customer satisfaction levels, maps service quality attributes, and identifies attributes experiencing stagnation or decline in service quality. The research adopts a quantitative approach through questionnaire distribution based on SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The instrument measures perceived service, desired service, adequate service, and the importance level of each service attribute. Data were analyzed using the Zone of Tolerance (ZOT) method through the calculation of Measure of Service Adequacy (MSA), Measure of Service Superiority (MSS), and ZOT values. The findings indicate that thirteen service attributes have met customer expectations or are within the tolerance zone, while seven attributes remain below the minimum acceptable service level and require immediate improvement. The priority attributes include cleanliness and comfort of facilities, employee appearance, completeness of office equipment, packaging availability, shipment coverage area, tracing facilities, and communication accessibility. The study highlights the importance of continuous service quality improvement to enhance customer satisfaction and competitiveness in the increasingly dynamic logistics industry.